Excavation and Study of an Intertidal Early Medieval Logboat, Langstone Harbour, Hampshire - Satchell, Julie (The international journal of nautical archaeology, 2025)
The excavation and investigation of an early medieval logboat and its environment within the intertidal zone of Langstone Harbour, UK, examined the boat remains, alongside worked and unworked wood located with it. Auger and seismic surveys revealed the logboat had been on the edge of a buried paleochannel, while palaeoenvironmental analysis demonstrated the area was silting up at the time the logboat was abandoned on an area of stabilised salt marsh. The results contribute to understanding the development of the harbour in addition to human activity in the area between the 5th and 7th centuries.